2012
DOI: 10.1016/j.expneurol.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity and axonal sprouting differentially regulate CNTF and CNTF receptor complex in the rat supraoptic nucleus

Abstract: We demonstrated previously that the hypothalamic supraoptic nucleus (SON) undergoes a robust axonal sprouting response following unilateral transection of the hypothalamo-neurohypophysial tract. Concomitant with this response is an increase in ciliary neurotrophic factor (CNTF) and CNTF receptor alpha (CNTFRα) expression in the contralateral non-uninjured SON from which the axonal outgrowth occurs. While these findings suggest that CNTF may act as a growth factor in support of neuronal plasticity in the SON, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 65 publications
(97 reference statements)
4
27
0
Order By: Relevance
“…We did not observe pSTAT3-immunoreactivity in magnocellular neurons following rrCNTF injection. This is in accordance with our previous observation that magnocellular neurons in the SON are not immunoreactive for LIFRß (Askvig, et al, 2012), which CNTF requires to mediate an intracellular signaling cascade (Davis, et al, 1993). Consistent with our results, neurons of the hippocampus, neocortex, cerebellar cortex, and olfactory bulb express CNTFRα and tSTAT3, yet CNTF administration does not lead to STAT3 activation within these neurons (MacLennan, et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We did not observe pSTAT3-immunoreactivity in magnocellular neurons following rrCNTF injection. This is in accordance with our previous observation that magnocellular neurons in the SON are not immunoreactive for LIFRß (Askvig, et al, 2012), which CNTF requires to mediate an intracellular signaling cascade (Davis, et al, 1993). Consistent with our results, neurons of the hippocampus, neocortex, cerebellar cortex, and olfactory bulb express CNTFRα and tSTAT3, yet CNTF administration does not lead to STAT3 activation within these neurons (MacLennan, et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…In support of this hypothesis we demonstrated that following axotomy CNTF and the CNTF receptor components are increased in the SON both during the period of axonal sprouting and neuronal injury (Askvig, et al, 2012). Others have shown that injury to the lens of the eye resulted in STAT3 activation in retinal ganglion cells along with elevated levels of endogenous CNTF in retinal astrocytes during the period of axonal regeneration in the rat retina (Muller, et al, 2007).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations